Systematic review: Landlords' willingness to retrofit energy efficiency improvements. (20th June 2021) - Lang, Michaela; Lane, Ruth; Zhao, Kun; Tham, Stephanie; Woolfe, Katrina; Raven, Rob
Abstract: Energy efficiency of privately rented homes is poorer than that of owner-occupied properties in many countries across Europe, North America and Australasia. Small-scale private landlords are the key decision makers for energy efficiency improvements for most rental properties. These landlords' energy efficiency retrofit decisions are poorly understood. This paper aims to synthesise existing research examining small-scale landlords' energy efficiency decisions. A systematic review was conducted according to the specifications of the PRISMA checklist. Sixteen academic and grey literature databases were searched, with 16 papers eligible for inclusion in the review. From these papers, a total of 47 factors were identified that potentially influence landlords' willingness to retrofit. The strongest available evidence relates to financial factors, which were more frequently studied than other factors. However, the wide range of factors identified in this review indicates that retrofitting in rental properties is not a purely financial consideration. Complexities in managing rental properties; landlord-tenant relationships; landlords' values, beliefs, and knowledge; and property market factors were all found to affect retrofitting. The paper highlights the need for landlord-specific energy efficiency research, particularly to confirm the influence of many factors in different social and regulatory contexts. A conceptual model of landlords' energy efficiency retrofitting behaviour is proposed.